Morphological changes of muscles of the crus and prevention of postoperative complications at patients with the diabetes mellitus at critical ischemia of the lower extremity - Bakhodir Barnoyevich Safoyev; Azizzhon Yakhyoevich Rakhimov; Razhabboy Isroilovich Isroilov (International Consortium of Education and Culture Research Studies, 2019)
The case history of 57 patients with critical lower limb ischemia in diabetes mellitus in the clinical database of the Bukhara State Medical Institute was studied. All examined patients were taken during surgery 2 grams of muscle tissue from m. soleus and m. gastrocnemius from one anatomical zone from the side of the amputated limb. Biopsy material was studied to determine the microflora and to predict the course of the wound process, and therefore the qualitative and quantitative content of the microbial bodies of the material was determined by bacteriological examination. The morphology of the soleus and biceps muscles was also studied. The results of the study showed a high growth of microbial bodies from the soleus muscle, the reason for this is necrosis of the muscle tissue, which was confirmed by the morphological study.